2018
DOI: 10.1515/chem-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flammulina velutipes (golden needle mushroom, eno-kitake) polysaccharides on constipation

Abstract: Flammulina velutipes, (Curt. ex Fr.) Sing, a popularly edible fungus, has been widely used both as a restorative drug and a tonic food in China. In the current study, the effect of F. velutipes polysaccharides was evaluated with a constipated rat model induced by loperamide hydrochloride. The rats were divided into six groups: normal group, model group, positive control group, F. velutipes polysaccharides high, moderate and low dose groups. Rats were given 2 mL of Loperamide hydrochloride (3 mg·kg·d), by intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In this study, constipation can reduce the mRNA levels of c‐Kit and SCF in rat small intestine and QCT could effectively upregulate the mRNA levels of c‐Kit and SCF ( p < .05), which rises the content of ICC in intestine of constipated rat, thus improving constipation. Previous evidence showed that the constipation is tightly correlated with the dysregulation of gastrointestinal motility‐mediating enteric neurons, ICC, and smooth muscle cells (Du et al., 2011; Xin et al., 2018). The neurotransmitters and peptides (such as MTL) released by the enteric nervous system can bind to the receptors on the ICC and promote slow waves generated in ICC to depolarize smooth muscle cells, generating GI contractions, and accelerating intestinal transit.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, constipation can reduce the mRNA levels of c‐Kit and SCF in rat small intestine and QCT could effectively upregulate the mRNA levels of c‐Kit and SCF ( p < .05), which rises the content of ICC in intestine of constipated rat, thus improving constipation. Previous evidence showed that the constipation is tightly correlated with the dysregulation of gastrointestinal motility‐mediating enteric neurons, ICC, and smooth muscle cells (Du et al., 2011; Xin et al., 2018). The neurotransmitters and peptides (such as MTL) released by the enteric nervous system can bind to the receptors on the ICC and promote slow waves generated in ICC to depolarize smooth muscle cells, generating GI contractions, and accelerating intestinal transit.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in noncovalent interactions on structures of proteins in the composite system have yet to be resolved, and few studies have investigated the noncovalent interactions in the complex of WPI and bioactive polysaccharides. Flammulina velutipes belongs to Tricholomataceae and is widely eaten in China and Japan [ 16 ]. Flammulina velutipes polysaccharides (FVPs) are regarded as one of the most important substances in Flammulina velutipes, which have been reported to possess a wide spectrum of biological activities including antioxidant and hepatoprotective activities, the ability to prevent Hepatitis B Virus (HBV) infection, and the capacity to induce immunity by activating macrophages [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides, as an important carbohydrate in nature, are from different sources, such as plant, fungi, and algae, and they exhibit different chemical and biological activities, depending on the structure and nature of the monosaccharides [1]. Due to the physicochemical and functional properties of polysaccharides, i.e., their water retention ability, filming capacity, antioxidant, anti-microbial, immunomodulatory, anti-cancer, constipation, and antithrombus activities [2,3,4,5,6,7], polysaccharides are used in a wide variety of industrial applications, such as food, pharmaceuticals, and textiles. However, inrecent years, due to its high molecular weight, polysaccharides have poor water solubility, so there has been increasing interest in water-soluble polysaccharides as an important class of bioactive substances that may compete with traditional polysaccharides due to their potential biological activities and processing properties.…”
Section: Introductionmentioning
confidence: 99%